Genetic variability of tambaqui broodstocks in the Brazilian state of Pará - Ferreira, Leandro de Araújo; Fazzi-Gomes, Paola Fabiana; Guerreiro, Sávio; Rodrigues, Marília Danyelle Nunes; Ribeiro-dos-Santos, Ândrea Kely; Santos, Sidney; Hamoy, Igor (Brazilian Journal of Animal Science, 2019)
The present study evaluated the genetic variability of the broodstocks of tambaqui hatcheries in the Brazilian state of Pará. Samples were obtained from the caudal fin of 110 broodstocks from one hatchery in each of four municipalities (Santarém, Peixe-Boi, Breu-Branco, and Ulianópolis), representing all the individuals of each hatchery stock. The samples were genotyped using the multiplex system microsatellite markers. Data were used to calculate observed and expected heterozygosity, number of alleles per locus, and allelic richness. The effective population size and inbreeding coefficient were also calculated. The genetic differentiation between populations was evaluated by using FST, and population structuring by the most likely number of genetically homogenous populations and Unweighted Pair Group Method (UPGMA); the arithmetic means were based on Nei’s. The indices indicated a loss of genetic variability in the broodstocks from Ulianópolis, Peixe-Boi, and Breu-Branco in comparison with wild tambaqui populations, although this was not apparent in the Santarém stock. A moderate level of genetic differentiation was found among the tambaqui broodstocks based on the FST estimates, which were reinforced by the structuring found in the Bayesian analysis and UPGMA. This reflects the domestication process, given that no such structuring is found in natural tambaqui populations. This moderate genetic differentiation associated with the loss of genetic variability found in the four tambaqui broodstocks from the state of Pará provides important insights for the development of future programs of genetic improvement, as well as the conservation of the genetic diversity of these stocks
Keywords: Colossoma macropomum; fish; genetic diversity; hatcheries